DNase I hypersensitivity in the gamma globin gene locus of K562 cells. - Lachman, H M (1983)
We have probed the chromatin conformation of the G gamma-A gamma-delta-beta globin gene locus of K562 cells, a human hematopoietic cell line, with the enzyme pancreatic DNAse I. This enzyme preferentially digests genes in an active configuration. We have found that in K562 cells, which produce embryonic and fetal but not adult hemoglobins, both the active gamma and inactive beta genes are DNAse I sensitive. However, only the active gamma genes have DNAse I hypersensitive regions. The hypersensitive regions have been mapped to an area approximately 100 base pairs 5' to the G gamma and A gamma genes.